Clinical, epidemiological and surgical characteristics of acute appendicitis in adult patients at hospital in Lima: Características clínicas, epidemiológicas y quirúrgicas de la apendicitis aguda en un hospital de Lima. - Cespedes , Carla (2023)
Mr. Editor: Acute appendicitis represents the most prevalent abdominal surgical condition globally, affecting approximately 10% of the population. Notably, its incidence is higher during the second and third decades of life, constituting the main cause of acute abdomen in the young adult population. In view of its prevalence, it is imperative that an early diagnosis be established and appropriate treatment applied to prevent associated complications. It is important to note that the mortality rate for uncomplicated cases is 0.6%, but it can rise to between 2-3% in cases of perforation and 5-15% in the elderly population.